Phosphorylation of the RNA polymerase II C-terminal domain by TFIIH kinase is not essential for transcription of Saccharomyces cerevisiae genome - Hong, Sun Woo (National Academy of Sciences, 2009)
Ser-5 phosphorylation of the RNA polymerase II (Pol II) C-terminal domain by TFIIH kinase has been implicated in critical steps in mRNA synthesis, such as Pol II promoter escape and mRNA 5′-capping. However, the general requirement and precise role of TFIIH kinase in Pol II transcription still remain elusive. Here we use a chemical genetics approach to show that, for a majority of budding-yeast genes, specific inhibition of the yeast TFIIH kinase results in a dramatic reduction in both mRNA level and Ser-5 C-terminal domain phosphorylation. Surprisingly, inhibition of TFIIH kinase activity only partially affected both Pol II density and Ser-2 phosphorylation level. The discrepancy between mRNA level and Pol II density is attributed to the defective 5′-capping, which results in the destabilization of mRNAs. Therefore, contrary to the current belief, our study points strongly toward a minor role of TFIIH kinase in Pol II transcription, and a more significant role in mRNA capping in budding yeast.